Non-response problem in health surveys - Shishir Kumar, Dr Shishir Kumar; Chhaya, Chhaya Gangwal; Avni Punia, Avni Punia (Social Determinants of Health, 2024)
The impact of non-participation in surveys depends on how many people don't respond and the extent to which those who don't differ from those who do on key questions. In health research, non-participation can skew results, affecting our understanding of disease and healthcare needs. Understanding why people don't respond to surveys is crucial for accurately gauging health issues. Despite the popularity of surveys in health research, the problem of non-response bias persists due to low response rates. This paper explores various methods, their strengths, and weaknesses, to address non-response issues in health surveys.